Flipped Classroom Model - PBL: Innovative Solutions to Improve Student Problem Solving - Miftahus Surur; Yesi Puspitasari; Siti Karunia Dewi (Nurul Jadid University, 2026)
The increasing integration of digital technology in higher education requires instructional approaches that can effectively develop students’ higher-order thinking skills, particularly problem-solving ability. This study examines the effect of integrating the Flipped Classroom model with Problem-Based Learning (PBL) on university students’ problem-solving skills. A quantitative approach was employed using a quasi-experimental design with a nonequivalent control group. The participants consisted of 66 undergraduate students enrolled in an Innovative Learning Media course, divided into an experimental group (31 students) and a control group (35 students). The experimental group was taught using the Flipped Classroom–PBL model, while the control group received conventional lecture-based instruction. Data were collected through pretests and posttests using a validated problem-solving test comprising non-routine essay questions, supported by observation sheets to ensure instructional fidelity. The data were analyzed using descriptive statistics, independent samples t-tests, and ANCOVA to control for initial differences between groups. The results indicate that students in the experimental group demonstrated a significantly greater improvement in problem-solving ability compared to those in the control group. These findings suggest that the integration of Flipped Classroom and PBL provides meaningful learning opportunities by encouraging active engagement, critical analysis, and collaborative problem-solving. This study contributes empirical evidence supporting the use of integrated active learning models as an effective strategy for enhancing problem-solving skills in higher education contexts.